Deep Brain Stimulation Hardware-related Infections: Ten-year Experience at a Single Institution - Abode-Iyamah, Kingsley O. (J Neurosurg, 2018)
OBJECTIVE: Deep brain stimulation (DBS) is an effective surgical treatment for managing some neurologic and psychiatric disorders. DBS hardware infection causes significant morbidity: hardware explantation may be required; initial disease symptoms such as tremor, rigidity, and bradykinesia may recur; and the medication requirements for adequate disease management may increase. These morbidities are of particular concern given that published DBS infection rates have been as high as 23%. To date, however, the key risk factors and potential preventive measures for these infections remain largely uncharacterized. METHODS: We performed a retrospective cohort study of patients undergoing primary DBS implantation at a single institution from December 2005 through September 2015 to identify possible risk factors for surgical site infection (SSI) and assess the impact of preoperative and intraoperative prophylactic antibiotics on the SSI rate. We also assessed the effect of a change in the National Healthcare Safety Network’s definition of SSI on the number of SSI detected. Statistical analyses were performed using the two-sample t-test, the Wilcoxon rank-sum test, the Chi-square test, the Fisher’s exact test, or logistic regression as appropriate for the variables examined. RESULTS: Two hundred forty-two adult patients had 464 electrodes placed during 245 primary procedures (most patients underwent bilateral electrode implantation) over approximately 10.5 years. Among these 245 procedures, nine infections (3.7%) occurred within 90 days and 16 (6.5%) occurred within one year of DBS placement. Gram-positive bacteria were the most common etiological microorganisms. The majority of patient- and procedure-related characteristics did not differ between patients that acquired SSI and those that did not. The rate of SSI among patients who received intra-wound vancomycin powder was only 3.3% compared to 9.7% among patients who did not receive topical vancomycin powder, and intra-wound vancomycin powder was associated with a decreased risk of SSI (odds ratio 0.32; 95% confidence interval [0.10 – 1.02]; P = 0.04). SSI rates were similar after staged and unstaged implantations. CONCLUSIONS: While most patient and procedure-related factors assessed in this study did not appear to affect the incidence of SSI, the data suggest that intra-wound vancomycin powder may help reduce SSI risk after DBS implantation. Furthermore, given the implications of SSI after DBS and the frequency of infections occurring greater than 90 days after implantation, continued follow-up for at least 1 year after these procedures is prudent to establish the true burden of these infections and to properly treat them when they do occur.